Political participation and city/county consolidation Jacksonville-Duval County. - Seamon, Fred; Feiock, Richard C. (1995)
"This article analyzes the effect of consolidation on the perception of power and influence in city and county government. It focuses specifically on the political effects of consolidated government by examining the extant literature and assessing the political impacts of consolidated government in Jacksonvile-Duval County. Using an interrupted time series analysis of voter participation, taxes, and expenditures were examined to determine the impact on consolidation and to explore the consequences of administrative reform"
Keywords: County government - Political activity - United States; Local government - United States